(untitled) (Journal of Organizational Psychology, 2017)
Trust is necessary for meaningful human existence and for various types of organizing, including business organizations, associations, charities, and, on a larger scale, the society itself. In this article, the focus is on organizational trust online – a specific form of trust that develops between individuals and organizations through interactions and various transactions conducted on the Internet. The author, following in the tradition that calls for building trust discursively, develops a theoretical basis for constructing organizational trust online and provides practical suggestions how to build organizational trust online and, consequently, promote establishing and building relationships with customers and prospective customers.